Prevalence of anxiety, depression, and stress among students of Jahangirnagar University in Bangladesh - Md. Moyazzem Hossain; Md. Asraful Alam; Monirul Hasan Masum (Health Science Reports, 2022)
Abstract Background and Aims Anxiety and depression, as well as stress, are well‐known problems observed across the world, particularly among students. This study intends to identify the level of anxiety, depression, and stress among university students and determine its association with their sociodemographic characteristics. Methods The primary data were collected from 351 students with the help of a self‐administrated questionnaire consisting of sociodemographic information and contains the Depression, Anxiety and Stress Scale‐21 Items (DASS‐21) instrument over the period December 8, 2019–January 23, 2020. The χ2 test is employed to find the association between the status of stress, anxiety, and depression level with selected sociodemographic variables, and confirmatory factor analysis is used to find interrelationships between DASS items. Results The results illustrate that no students have an extremely severe level of stress. However, the majority have a mild or moderate level of stress and it is associated with sex and residence (urban or rural). More than 40% of students have extremely severe anxiety. Results reveal that gender, residence (urban or rural), and family type of the students are linked with the anxiety level. The results also suggest that the type of accommodation of the students, their family type, and birth order are related to their depression level at a 5% level of significance. The findings also disclose that female students have more levels of depression, stress, and anxiety than their counterparts. Conclusion Considering the finding, the authors think that the university authority should pay a need for greater interest to the mental well‐being of students to enhance their quality of life. Given the harmful impacts of stress on academic performance and health, university administrators should be incorporating anxiety, stress, and depression management training in orientation activities.